Simultaneous dislocation of both the proximal and distal interphalangeal joints of a little finger. (1st February 2016) - Abdelaal, Ahmed; Edwards, Tomos; Anand, Sambandam
Abstract : A 39-year-old man fell at work sustaining dislocation of both the proximal and distal interphalangeal joints of his left little finger. The injuries were assessed and treated with closed reduction and stabilised by buddy taping. Early active range of movement was encouraged and a referral to physiotherapy was made. At the final follow-up, 4 months after the injury, he lacked subtle end of range movement actively, but functionally he was coping well and had made a full return to work.